The Relationship between the Perceived Parenting Styles and Self-esteem among Secondary School Students in Zanzibar - Eldaffa, Eltaher Ali Eltaher; Bakari, Aboubakari Bashiru; Mchuchuli, Mwanaidi Ramadhani; Sangalala, Leticia Nestory; Othman, Sumaiya Mohamed; Jabil, Salumu Amour (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
This research aimed to examine the relationship between perceived parenting styles and self-esteem, the relationship between parenting style and self-esteem, and the differences between male and female self-esteem among secondary school students in Zanzibar. A quantitative research approach was employed, involving a sample of 100 students selected from various secondary schools 40 male and 60 female. Data were collected using two standardized instruments: the Rosenberg Self-Esteem Scale (RSES) to assess the level of self-esteem, and the Perceived Parenting Styles Scale to evaluate students’ perceptions of their parents’ parenting styles. The data manipulated Statistical Package for Social Sciences (SPSS) through, T.test one sample, T.test two independent sample and the results show that there is no statistically significant relationship between perceived parenting styles and self-esteem among the students. However, the overall level of self-esteem among the participants was found to be high. Additionally, the perceived parenting styles were generally characterized positively, indicating a constructive perception of parental behaviors. Notably, the study identified a statistically significant difference in self-esteem levels between male and female students, suggesting gender as a relevant factor in adolescents’ self-perception.These results highlight the complexity of factors influencing self-esteem among adolescents and suggest the need for further research into other contextual and psychosocial variables. The study also recommends the development of gender-responsive programs that support students’ emotional and psychological well-being across different backgrounds